Materiality of language in jain philosophy: introductory matters - Glinicka, Małgorzata (Hybris, 2016)
The aim of this article is to describe the concept of language materiality in the Jain philosophy, focusing on the literature of classical period (5th-10th c. CE). I concentrate on the following texts: Viyāhapannatti, Ālāpa-paddhati, Tattvârtha-sūtra, Tattvârthasūtra-rājavārttika etc. I take into account diverse questions such as: multidimensionality of reality, attendance of matter, the theory of molecules (vargaṇās) and the problem of matter modifications (pariṇāma).